Adherence to Mediterranean diet among Lithuanian and Croatian students during COVID-19 pandemic and its health behavior correlates - Brigita Mieziene; Greta Burkaite; Arunas Emeljanovas; Ilona Tilindiene; Dario Novak; Ichiro Kawachi (Frontiers Media S.A., 2022)
Maintaining healthy behavior, especially in times of crisis like the COVID-19 pandemic, is particularly important for staying healthy. Nutrition is an everyday behavior and along with other health-related behaviors is associated with many health outcomes. The aim of this study was to assess and compare adherence to the Mediterranean diet (MedDiet) and particular food choices among the Mediterranean and non-Mediterranean populations of university students and identify its lifestyle correlates at the outburst of the COVID-19 pandemic. In total, self-reported data on health-related behavior and sociodemographic characteristics were collected from 1,388 study participants, 66.4% were Lithuanians, and 33.6% were Croatians. Results revealed that vegetables, olive oil, fruits, nuts, legumes, and fish were remarkably underconsumed among university students in the Mediterranean and non-Mediterranean countries during the COVID-19 pandemic, and the composite diet is similar between countries. The higher adherence to MedDiet is associated with physical activity (β = 0.15) and non-smoking (β = 0.08). In times of crisis, public health entities should provide knowledge, skills, and tools for healthy nutrition specifying them by age and subpopulation. Interventions at the university should be implemented to build infrastructure and provide an access to health behavior-friendly environments.